Beyond reactive responses to enduring growth: the transformation of principles and practices within initial teacher education - Burn, K; Ingram, J; Molway, L; Mutton, T (Taylor and Francis, 2022)
A previous special issue of this journal (Vol 46, 4) demonstrated the significant challenges for programmes of initial teacher preparation unleashed by the Covid-19 pandemic. After forcing urgent changes, the pandemic also prompted some teacher-educators to reconsider fundamental principles underpinning their programmes, as they decided which innovative approaches to retain. Using an established model of professional growth that distinguishes between temporary ‘change sequences’ and enduring ‘growth networks’, this paper examines how opportunities for learning afforded by the pandemic were transformed into sustained professional growth. Adaptions in response to successive waves of infection created a continuously evolving ‘change environment’, stimulating new kinds of pedagogy while affording or constraining different kinds of feedback on its effectiveness. We consider published examples of professional responses to this changing context alongside vignettes from our own professional practice to examine what is needed for teacher-educators to move beyond crisis management, recognising opportunities for sustained growth. By focusing on different emphases given at different points to the processes of enactment and reflection, we explore the extent to which teacher-educators went on to interrogate the established principles of their teacher education programmes and we consider the potential impact of such interrogations.